Picture-Based Vocabulary Cards for Enriching Students' Vocabulary with Mild Intellectual Disability (Scripta : English Department Journal, 2026)
This study explores the use of picture-based vocabulary cards in teaching English vocabulary to students with mild intellectual disabilities in Sekolah Luar Biasa (SLB), a special education school in Indonesia that provides educational services for students with various disabilities. This study aims to investigate how teachers implement picture-based vocabulary cards and identify the challenges they face in the teaching process. A qualitative descriptive research design was employed, involving two teachers with different educational backgrounds. Data were collected through semi-structured interviews and classroom observations, then analyzed thematically. The findings revealed that picture-based vocabulary cards are used as one of the instructional media; however, their use is not dominant, as teachers tend to combine them with other media such as real objects and videos to support students’ understanding. Students showed varied responses depending on their individual abilities, with some actively engaging while others required more repetition and guidance. Several challenges were also identified, including differences in students’ abilities, limited attention span, and difficulties in vocabulary retention. Thus, while picture-based vocabulary cards are useful, their effectiveness depends on how they are integrated with other instructional strategies and adapted to students’ needs. This study contributes to English language teaching in special education by providing insights into teachers’ practices in SLB contexts.